Hepatitis B immune status in adolescents vaccinated during infancy: A retrospective cohort study from a pediatric practice in Germany. Issue 3 (3rd March 2016) - Anderson, Carrie L.; Remschmidt, Cornelius; Drobnitzky, Frank-Peter; Falkenhorst, Gerhard; Zimmermann, Ruth; Wichmann, Ole; Harder, Thomas
Abstract: In Germany, vaccination of infants against hepatitis B is recommended since 1995. However, data on long-term immunity is sparse and the necessity of a booster dose remains uncertain. Aims of this study were to assess the long-term persistence of antibodies to the hepatitis B surface antigen (anti-HBs) after immunization during infancy and the effect of a subsequent hepatitis B booster vaccination during adolescence on anti-HBs levels. Patients from a private pediatric practice who had received a full vaccination course of hepatitis B as infants and who were quantitatively tested for anti-HBs during adolescence (pre-booster levels) were included. In those participants who received a hepatitis B booster, post-booster anti-HBs levels were measured. Univariate analyses were conducted to determine factors associated with pre- and post-booster anti-HBs levels, respectively. 106 participants (53% male) were included in the study. At an average of 13.7 y after primary vaccination, 14% of participants had an anti-HBs level of ≥100 IU/l, while 46% were at 10–99 IU/l and 40% had anti-HBs levels of <10 IU/l. In total, 34 received a booster vaccination. Of those, 97% (33/34) had post-booster anti-HBs levels ≥ 100 IU/l, which were independent from pre-booster levels. No other patient characteristics were associated with pre-booster or post-booster anti-HBs≥ 100 IU/l. Although almost half of study participants showed low anti-HBs levels at follow-up, robust responses to booster vaccination suggest that adolescents who received the full vaccination course during infancy are still protected against hepatitis B infection.